Diverse developmental trajectories of perineuronal nets during vertebrate nervous system construction - Edwards, Jacob, author; Hoke, Kim, advisor; Anderson, Charles, committee member; Garrity, Deborah, committee member; Mueller, Rachel, committee member (Colorado State University. Libraries, 2018)
In the central nervous system, aggregated extracellular matrix compounds known as perineuronal nets (PNNs) shape patterns of neural connectivity over development. Removing PNNs restores juvenile-like states of neural circuit plasticity and subsequent behavioral plasticity. Our current understanding of the role of PNNs in plasticity has resulted in promising therapeutic applications for many neurodegenerative diseases. To ensure safety and efficacy in such applications, we require a broad understanding of PNN function in the nervous system. The current data suggest that PNNs stabilize fundamental features of neural connectivity progressively in an ascending, or "ground-up", fashion. Stabilizing lower input processing pathways establishes a solid, reliable foundation for higher cognition. However, data on PNN development exists almost exclusively for mammals. Is, then, the ground-up model of circuit stabilization a general feature of PNNs across vertebrates? I found that developmental patterns of PNNs in fish (Poecilia reticulata), amphibians (Rhinella yunga), and reptiles (Anolis sagrei) follow diverse trajectories, often emerging first in higher forebrain processing pathways. Similarly, they associate with diverse cell populations and vary widely in structural characteristics both within and across species. While my data do not invalidate a ground-up model for mammal PNNs, they do suggest that this pattern may be an evolutionary innovation in this group, and that the broad roles of PNNs in circuit stability and neuronal physiology are complex and lineage-specific.